Gardner Syndrome imaging features in plain radiographs and computed tomography: a case report - Munhoz, Luciana; IIda, Christyan Hiroshi; Arita, Emiko Saito; Watanabe, Plauto Christopher Aranha (Brazilian Dental Science, 2020)
Gardner syndrome (GS) is a genetic disease with high penetrance characterized by a signal triad of colonic polyposis, multiple osteomas and mesenchymal tumors in the soft tissues and skin. The colonic polyposis is associated to the development of malignant disease. Patients also may present maxillomandibular alterations such as impacted teeth, supernumerary teeth, congenital missing teeth and odontomas. Bone lesions and maxillomandibular alterations usually precedes the gastrointestinal alterations; hence dentists should be aware of GS syndrome main radiographic signals  , in order to detect the disease and proper referred the patient to medical treatment and surveillance. Thus, in this report, it is demonstrated a case of GS in a male patient, as well as discussed GS features.